Study of the determinants of chronic malnutrition in northern Nigeria: Quantitative evidence from the Nigeria demographic and health surveys - Amare, Mulubrhan; Benson, Todd; Fadare, Olusegun; Oyeyemi, Motunrayo (SAGE Publications, 2018)
Close to half of all children younger than 5 years in the Northeast and Northwest geopolitical zones were estimated to be stunted in their growth for their age in 2013 compared to 22% of children in the rest of Nigeria.We examine the drivers of chronic child undernutrition in northern Nigeria and how those drivers differ from other areas of the country.Both a standard child-level regression-based approach and decomposition analysis were used to address the determinants of stunting and decompose how drivers differ between northern Nigeria and other areas of the country using 2008 and 2013 Nigeria DHS data.There are strong differences in the levels of the determinants of undernutrition in young children between the 2 parts of the country. However, equally important, the decomposition analysis shows that there are significant differences between northern Nigeria and other areas of Nigeria in the effect of the same determinant of nutritional status in accelerating or retarding the linear growth of young children.A national program to address child undernutrition must recognize this heterogeneity in its design. To impose across Nigeria, a single set of approaches to address the factors which results in stunted children is likely to fail for large numbers of children if these strong geographical differences in how these determinants operate to affect child nutritional status are not considered. Solutions need to be developed within northern Nigeria to more closely reflect the way the determinants of nutritional status operate in this area of the country.